(untitled) (Fiep Bulletin - online, 2015)
The control of the sporting training if constitutes essential element in the improvement of the income, which depends on the adequate perfectioning of the displacement speed. The motor speed, understood as a capacity human being who conditions the accomplishment of the porting movements, constitutes a factor of the income to which if it has attributed great importance. Trainers and investigators have come back its concerns, toward the forms of manifestation that characterize it, but also for the way of them to not only transform into inductors of efficiency and effectiveness of the porting actions. The measurement of this physical quality requires the use of tests that supply to theoretical subsidies that contribute in the load application of determined orientation, facilitating the dialogue most coherent with the specific of each sporting modality. The aim of this study was to compare the performance of different systems of measurement (chronometer, plates of contact, photocells, tachometer and system of rope) in the speed test. For in such a way, a composed sample for 8 volunteers, who had been submitted the 4 races of 20 meters, from which was used if the average speed of the passage registered. The analysis of the results demonstrated one high correlation between the averages gotten for the different mechanisms of measurement and the general average (composed for all instruments), disclosing the effectiveness of the same ones in the register of the speed in the distance of 20 meters. The tachometer presented significant difference when comparative with the results gotten for the other tested systems.